The online newspaper user: young, affluent and online savvy? - Vagg, Trevor (Henry Stewart Talks, 2010)
How is the online newspaper audience different from the audience for printed newspapers, Online versions increase newspaper reach overall, Differences in attitudes and behaviour between online newspaper users and the broader online audience
Archived at 2022/11/27